2005
DOI: 10.1080/13816810500229025
|View full text |Cite
|
Sign up to set email alerts
|

Mild Optic Nerve Hypoplasia with Retinal Venous Tortuosity in Aarskog (Facial-Digital-Genital) Syndrome

Abstract: Aarskog syndrome (faciogenital dysplasia) is an X-linked recessive genetic growth disorder characterized by short stature, dysmorphic facies, shawl scrotum, and digital anomalies. The condition was first described in 1970 and the gene responsible is FGD1 (MIM#305400). There are several reported ophthalmic findings associated with Aarskog syndrome which are discussed. We describe a case of Aarskog syndrome with venous tortuosity, optic nerve hypoplasia, and a type-2 antithrombin deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Although this anomaly has been described in several genetic disorders, this seems to be the first case of AAS associated with congenital glaucoma. Although various ocular manifestations have been reported in AAS before [Kirkham et al, 1975; Brodsky et al, 1990; Pizio et al, 1994; Jogiya and Sandy, 2005; Taub and Stanton, 2008], Nevertheless, two patients with the same mutations (Patients 6 and 8) do not present with a similar ocular features and this finding may therefore be co‐incidental.…”
Section: Discussionmentioning
confidence: 96%
“…Although this anomaly has been described in several genetic disorders, this seems to be the first case of AAS associated with congenital glaucoma. Although various ocular manifestations have been reported in AAS before [Kirkham et al, 1975; Brodsky et al, 1990; Pizio et al, 1994; Jogiya and Sandy, 2005; Taub and Stanton, 2008], Nevertheless, two patients with the same mutations (Patients 6 and 8) do not present with a similar ocular features and this finding may therefore be co‐incidental.…”
Section: Discussionmentioning
confidence: 96%
“…3, 37, 40 Development of tortuous retinal veins and varicose veins has been linked to venous disease and genetic deficiency. 24, 28, 31, 38 However, the relationships between venous pressure, vascular wall degradation, and vein tortuosity were poorly understood. Our current results indicated that mechanical buckling could be a possible initiation mechanism for the development of tortuous veins.…”
Section: Discussionmentioning
confidence: 99%
“…Though rare, tortuosity has also been observed in other vascular branches in the arterial tree. These branches include, but are not limited to: the ulnar artery and radial and digital arteries[17,18,19]. It seems that tortuosity can affect almost all medial-sized arterial branches.…”
Section: Symptomsmentioning
confidence: 99%